1993
DOI: 10.5014/ajot.47.8.686
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Functional Performance

Abstract: We compared the functional performance of 20 young adult women and 20 older adult women on two types of tasks. One type of task was normal instrumental activities of daily living (e.g., meal preparation, home maintenance) that were meaningful, familiar, and well practiced. The other type was a contrived, relatively unfamiliar task of wrapping a package. Although young and old women did not differ significantly in their familiarity with the two tasks, results from two repeated measures MANOVAs revealed a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 25 publications
5
41
0
2
Order By: Relevance
“…This stands in contrast to work by Lyness et al (1993), who found the depression to be the most dominant factor, but also found that age and gender factors were associated with decline in function. The moderate negative correlation between IADL performance and age that was found in the normal control group supports Dickenson and Fisher's (1993) findings. The findings in this current study that the IADL dysfunction induced by depression was more dominant than the age factor is congruent with a study reported by Forsell and colleagues (1994).…”
Section: Discussionsupporting
confidence: 82%
“…This stands in contrast to work by Lyness et al (1993), who found the depression to be the most dominant factor, but also found that age and gender factors were associated with decline in function. The moderate negative correlation between IADL performance and age that was found in the normal control group supports Dickenson and Fisher's (1993) findings. The findings in this current study that the IADL dysfunction induced by depression was more dominant than the age factor is congruent with a study reported by Forsell and colleagues (1994).…”
Section: Discussionsupporting
confidence: 82%
“…However, cognitive state as expressed in MMSE scores is a substantial element, explaining about 65% of the variance in performance of ADL and IADL as expressed in the KELS scores. This finding shows that cognitive factors have a substantial influence on IADL performance, as documented in the literature (Dickerson and Fisher, 1993;Christensen et al, 1996;Levy, 1998), and should be considered in any evaluation of elderly individuals.…”
Section: Discussionsupporting
confidence: 69%
“…Tr ombly (1992) suggested the use of kinematic analysis of movements and associated muscular responses (electromyography) to quantify and document motor performances as these analyses could reveal the movement strategy adopted by the nervous system to perform the movement. Since occupational therapists involved in adult neurorehabilitation primarily treat elderly populations, kinematic studies of daily tasks involving the well elderly population will be especially useful to form a baseline (Dickerson and Fisher, 1993;Nilsen et al, 2003) for research as a way to validate evidence-based practice (Holm, 2000;Tickle-Degnen, 2000).…”
Section: Introductionmentioning
confidence: 99%